(untitled) (Indian Journal of Fibre & Textile Research (IJFTR), 2026)
The aim of this study is to investigate the effectiveness of reactive monochlorotriazine β-cyclodextrin (MCT β-CD) in developing durable, fragrance-finished cotton fabrics using clove essential oil applied through solvent and nanoemulsion techniques. Natural essential oils offer desirable sensory and functional attributes; however, their limited durability on textiles necessitates the development of suitable microencapsulation systems. In this work, MCT β-CD is synthesised from β-CD and cyanuric chloride, characterised using FTIR, TGA, SEM, EDS and XRD, and subsequently covalently grafted onto cotton under alkaline conditions. Optimal fixation is achieved using a 70 g/L MCT β-CD solution, as determined through add-on percentage, wash durability and phenolphthalein absorbance analysis. Clove oil is applied to the MCT β-CD finished cotton using both ethanol-based solvent treatment and a sustainably formulated nanoemulsion. The retained oil content is quantified after atmospheric exposure and multiple wash cycles. Results show that MCT β-CD exhibits strong covalent bonding with cotton, resulting in significantly enhanced durability for clove oil through the formation of an inclusion complex. The nanoemulsion method performs comparably to the solvent method, offering an effective and environmentally benign alternative for essential-oil finishing. Thus, the nanoemulsion technique can be utilised efficiently as a sustainable alternative to toxic solvents in essential oil applications, resulting in MCT β-CD finished textiles with multifunctional properties.